2011
DOI: 10.1007/s00464-011-2046-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-assisted versus conventional second branchial cleft cyst resection

Abstract: Endoscope-assisted second branchial cleft cyst resection via retroauricular approach is a feasible technique. This procedure may serve as an alternative approach that allows an invisible incision and better cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 20 publications
0
49
0
2
Order By: Relevance
“…14 In addition, several authors have reported the use of a retroauricular incision for robotic facelift thyroidectomies or benign neck mass excision with or without endoscopy. 6,15,16 In this study we used a postauricular facelift incision for selective neck dissection including levels I-III and found this allowed a clear and sufficient surgical view of levels I-III. Complete dissection of level IIB and high level IIA was also possible under direct vision without the da Vinci robot.…”
Section: Discussionmentioning
confidence: 95%
“…14 In addition, several authors have reported the use of a retroauricular incision for robotic facelift thyroidectomies or benign neck mass excision with or without endoscopy. 6,15,16 In this study we used a postauricular facelift incision for selective neck dissection including levels I-III and found this allowed a clear and sufficient surgical view of levels I-III. Complete dissection of level IIB and high level IIA was also possible under direct vision without the da Vinci robot.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the surgical flap aspect ratio was small, and the flap was thicker. Moreover, the thicker flap has a smaller risk for necrosis [5]. In the present study, there were no flap necrosis or postoperative color change cases.…”
Section: Discussionmentioning
confidence: 46%
“…Thus, the function of many parotid and cosmetic surgery scholars has been to develop new surgical techniques. Endoscopy has been used in thyroid [6], submandibular gland [7] and branchial cleft cyst surgeries [5]. The successful application of endoscopies during neck surgery made parotid endoscopic surgery possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They all resulted patient satisfaction. [16][17][18][19] Lin et al 9 reported the first endoscopeassisted parotidectomy with a 60-81-mm modified ''S''-incision, which, however, was still visible. In recent years, some researchers have developed the endoscope-assisted parotidectomy, with a more subtle incision for benign parotid disease.…”
Section: Discussionmentioning
confidence: 99%